Praktik Akad Istishna' Paralel dalam Jual Beli Rumah di PT. Berkah Rangga Sakti Kecamatan - Buhari , Taufiq (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
Today the need for a place to live is a factor in the community to meet their daily needs, even though they do not have enough money, people are competing to own a house, so that many people get a place to live by paying in installments with various systems in their respective places of residence. Application of a parallel istishna 'contract in buying and selling houses in a company PT. Berkah Rangga Sakti, which is engaged in selling houses, has met the requirements and principles that apply in the shari'ah economy. But in the financing of PT. Berkah Rangga Sakti did not use a Syari'ah Bank but a conventional bank due to the difficulty of accessing the Syari'ah Bank, which provides home financing in the Bangkalan area.